Pengaruh kecepatan potong terhadap keausan dan panjang pemakanan mata pahat keramik alumina pada pembubutan cast iron - Nistelroy, A.R.; Lubis, S.Y.; Riza, A. (Universitas Mataram, 2024)
Turning is a metal forming process to produce cylindrical machine parts made using a lathe machine. Cast iron is one of the materials that has hard and brittle properties, therefore a harder and tougher type of cutting tools is needed. One type of cutting tools that has hardness and resistance to high temperatures is alumina-based ceramic. This study aims to analyze the alumina ceramic cutting tools by determining the level of wear that occurs with various cutting variables in cast iron turning. The experiment was carried out using a conventional lathe while the tool used was an alumina-based ceramic tool with a dry turning process without cooling. The cutting parameters used were cutting speed: 141.3 m/min, 222.9 m/min, 351.6 m/min, Spindle rotation: 450 r/min, 710 r/min, 1120 r/min, Depth of Cut: 0.1 mm, Cutting Resistance: 0.1 mm. The turning process was carried out with a time span of 5 minutes and then the tool wear value (Vb) was measured at 0.3 mm. The experimental results showed that at a cutting speed of 141.3 mm/min, the tool wear was 0.3 mm with a total feed length of 1575 mm for 35 minutes. At Vc 222.9 mm/min the tool wear was 0.35 mm with a total feed length of 1420 mm for 20 minutes. At Vc 351.6 the tool wear was 0.32 mm with a total feed length of 1680 mm for 15 minutes.